Pemanfaatan Kolagen Tulang Ayam Broiler dalam Sediaan Serum: Nilai SPF, Eritema, Pigmentasi, Kelembapan Kulit - Suleman, Abdul Wahid; Safaruddin, Safaruddin; Mustamin, Sharnawati; Wahyuningsih, Sri; Jannah, Miftahul (Journal of Pharmaceutical and Health Research, 2025)
Chicken bones (Gallus gallus domestica) are a type of solid waste that contain protein sources in the form of collagen. Collagen is one of the main connective tissue proteins in animals, widely used as a biomedical material, and is effective as an anti-aging agent that helps prevent the appearance of aging signs on the skin. This study aims to determine the potential of broiler chicken bone collagen in serum formulations as a photoprotective, anti-pigmentation, and skin moisturizing agent. The research method used was an in vitro experimental method using a UV-Vis spectrophotometer. Collagen was extracted using NaOH and CH₃COOH 1 M, and serum formulations were prepared with concentrations F1 (1%), F2 (1.5%), F3 (2%), and F4 (2.5%). The SPF value, erythema and pigmentation levels, as well as skin moisture, were then determined. The results of the serum formulation showed physical and chemical stability, indicated by no significant differences before and after the cycling test in organoleptic, pH, homogeneity, viscosity, and spreadability evaluations. The SPF values of the serum preparations were: F1 (1%) = 2.814999, F2 (1.5%) = 3.287317, F3 (2%) = 4.659954, and F4 (2.5%) = 8.574363. The %Te and %Tp tests showed that F0 (without extract) fell under the “Sunblock <1” category, while F1, F2, F3, and F4 were categorized as “Fast tanning” with values between 45–86. In conclusion, this study demonstrates that chicken bone extract can be formulated into a serum preparation that is physically and chemically stable. The best SPF, %Te, and %Tp values were obtained in the F4 formula, categorized as optimal, with %Te and %Tp values in the fast tanning category. Additionally, the F4 formula increased skin moisture by 5%.